(untitled) (Research, Society and Development, 2021)
The text is about effects of Cyclone Idai on the dietary diversity, in the district of Sussundenga in Mozambique. Considering that it has been appointed as the breadbasket of the province, if it’s has been assumed that there is dietary diversity. The question is why there are malnourished children when supposedly there is diversity of food, and in particular, how Cyclone Idai may have contributed for its aggravation. The objective was to analyze the effects of the Cyclone on dietary diversity, using non-participant observation and annotation in a field diary, a Dietary Diversity Questionnaire and an interview guide. The study involved 131 mother’s schoolchildren, four community leaders and a representative from the Agriculture sector. It took place between September 2018 and October 2019. It was found that the effects of cyclone was on production, availability and access to food, since the differences in the averages were significant, and may have contributed to the expansion of difficulties for a diversified diet, which may have resulted in rising rates of child malnutrition. The cyclone affected the diet of the families. It’s important to prioritize agriculture and livestock breeding for food consumption, improving food diversity, especially the protein source, to prevent child malnutrition.